RIBEYRO, SURVIVING IN THE TRENCHES THE BOOM - Valero Juan, Eva Maria (2005)
It is only recently that Ribeyro has been extensively published. He hasalso received recognition from the academic world, especially fromEuropean critics. In this article, is it shown that, even when Ribeyrodisdained up-to-date recipes and technical novelties, his work stands asmodem as ever. A proposal to consider Ribeyro's urban imagining asanirradiating axis of fundamental questions is here substantiated.